In vivo printing of growth factor-eluting adhesive scaffolds improves wound healing - Kristo Nuutila (KeAi Communications Co., Ltd., 2022)
Acute and chronic wounds affect millions of people around the world, imposing a growing financial burden on patients and hospitals. Despite the application of current wound management strategies, the physiological healing process is disrupted in many cases, resulting in impaired wound healing. Therefore, more efficient and easy-to-use treatment modalities are needed. In this study, we demonstrate the benefit of in vivo printed, growth factor-eluting adhesive scaffolds for the treatment of full-thickness wounds in a porcine model. A custom-made handheld printer is implemented to finely print gelatin-methacryloyl (GelMA) hydrogel containing vascular endothelial growth factor (VEGF) into the wounds. In vitro and in vivo results show that the in situ GelMA crosslinking induces a strong scaffold adhesion and enables printing on curved surfaces of wet tissues, without the need for any sutures. The scaffold is further shown to offer a sustained release of VEGF, enhancing the migration of endothelial cells in vitro. Histological analyses demonstrate that the administration of the VEGF-eluting GelMA scaffolds that remain adherent to the wound bed significantly improves the quality of healing in porcine wounds. The introduced in vivo printing strategy for wound healing applications is translational and convenient to use in any place, such as an operating room, and does not require expensive bioprinters or imaging modalities.